Sistem Informasi Perjalanan Dinas Subdit Pengembangan Permodalan dan Investasi - Sudradjat, Adjat; Rokhayati, Erna; Hariyanto, Hariyanto (Politeknik Ganesha Medan, 2018)
Official travel is an activity undertaken by employees relating to official duty in accordance with the order within a specified time period. The official travel administration system on the Sub Direktorat Pengembangan Permodalan dan Investasi is still done conventionally, it is done by correspondence from the permit filing stage to the reporting stage of official travel results. This makes the length of the recording flow of official travel administration data, thus stalling from the time already scheduled. This study aims to build a web-based travel information system on the Sub Direktorat Pengembangan Permodalan dan Investasi, as a means of service administrative process of travel official service online. The discussion focuses on the process of applying for official travel, the calculation of the number of days and the cost of official travel, official travel approval and disposition of official travel expenses through a web-based application whose system development methods use the waterfall model. With an online travel information service system, employees can apply for official travel permits more easily, the management can give approval and disposition of the official travel fee payment more quickly. Effectiveness and efficiency can be achieved in the fulfillment of official travel targets, in accordance with predetermined schedule and approved budget.